Developing the non‐dimensional framework for water distribution formulation to evaluate sprinkler irrigation - Li, Ang; Mu, Xinyuan; Zhao, Xia; Xu, Jiamin; Khayatnezhad, Majid; Lalehzari, Reza (Irrigation and drainage, 2021)
Improving the application efficiency and leaching of solutes from the root zone in a sprinkler irrigation system are directly related to the uniformity of water distribution at the field surface. The coefficient of uniformity and distribution uniformity are affected by changes in wind speed and its direction, sprinkler characteristics and variations in operating pressure. The objective of this paper is to present modified equations for evaluating pressurized irrigation systems based on non‐dimensional infiltrated depths. The equations were obtained by four data groups including the average of the measured infiltration depths in any quarter. Coefficient of uniformity (CU), distribution uniformity (DU), application efficiency (Ea) and deep percolation (DP) were used as performance indicators to evaluate the sprinkler irrigation system. The suggested method was compared to the existing approach to assess the evaluation indicators. Three data sets of observed information for wheel‐move, permanent solid set and semi‐solid set irrigation systems were collected in Chaharmahal and Bakhtiari provinces to evaluate the proposed formulation. Furthermore, the relationships between CU and DU were analysed for three scenarios of infiltration depth. Results show that the application efficiency was 12% less than previous equations because of using four average values. Résumé L'uniformité de la distribution de l'eau en irrigation par aspersion est un facteur d'évaluation important qui affecte l'efficacité de l'application et la lixiviation des solutés. Le coefficient d'uniformité et l'uniformité de la distribution sont affectés par les changements de vitesse du vent et de sa direction, les caractéristiques des arroseurs et les variations de la pression de service. L'objectif de cet article est de présenter des équations modifiées pour évaluer les systèmes d'irrigation sous pression basés sur des profondeurs infiltrées adimensionnelles. Les équations ont été obtenues par quatre groupes de données, y compris la moyenne des profondeurs d'infiltration mesurées dans n'importe quel trimestre. Le coefficient d'uniformité (CU), l'uniformité de la distribution (DU), l'efficacité de l'application (Ea) et la percolation (DP) ont été utilisés comme indicateurs de performance pour évaluer le système d'irrigation par aspersion. La méthode suggérée a été comparée à l'approche existante pour évaluer les indicateurs d'évaluation. Trois ensembles de données d'informations observées pour les systèmes d'irrigation à pivot, rampe et couverture intégrale ont été collectés dans les provinces de Chaharmahal et Bakhtiari pour évaluer la formulation proposée. De plus, les relations entre le CU et le DU ont été analysées pour trois scénarios de profondeur d'infiltration. Les résultats montrent que l'efficacité de l'application était inférieure de 12% aux équations précédentes en raison de l'utilisation de quatre valeurs moyennes.